Mitigation and Adaptation Analysis of the Climate Change Impact Using Sustainable Livelihood Model - Ayu Puspito Sari, Deffi; Falatehan, Faroby; Surya Irawan, Diki; Sedana, Gede; Rahim, Robbi (International Journal of Engineering and Technology, 2018)
This study aims to identify and analyze the farmers’ perception of the climate variability and the impacts of the climate variability, identify and analyze the vulnerability and the income of the farmers due to the climate variability, identify and analyze the farmer strategy in anticipating and adapting the climate variability and recommending the adaptation mechanism based on engineering, institutional, technological, social, economic, and cultural organizations to the farmer in responding to the climate variability. Most of the farmers know and understand the climate change information from the television. Farmers mostly feel this climate change through the increase in temperature and the number of dry days. The impact of the climate change affects the livelihood of the farmers, not a few farmers suffered the losses due to the decreased in productivity. To reduce the decrease in income, the farmers increase the use of input, thus affecting the income of the farmers. The results of a comparison of the farmers between 2009 and 2015, there is an increase in productivity and revenue, but this increase is lower than the increased costs incurred by the farmers. This resulted in lower revenues of the farmers in 2015 than in 2009. There are 3 kinds of the strategies which is undertaken by the farmers: economic, ecological and social adaptation. For the economic adaptation, the expectations of the farmers to the capital assets are higher than the actual condition. Ideally, the highest ideal expected by the farmers is physical capital, while the lowest is social capital. Meanwhile, for the ecological adaptation, the community seeks to improve the irrigation channel, replace commodities and utilize the appropriate technology. As for the social adaptation, farmers are expecting the help from the government.  The policy implications from this research are: 1) the farmer in Jatiluwih are mostly aware of climate change, some strategies have been implemented by the farmers to maintain their income that affected by the climate change such as to work in the city or become a tour guide in their area. Based on the analysis of the sustainable livelihood, the farmers' expectation of physical capital such as electricity, water, irrigation, and roads are relatively high compared to the other capital. Because of the cost of supply is high, the provision of the physical capital is not easy, the government intervention is needed. Therefore, the farmers are expecting the government to be able to improve the condition of these facilities, especially for the irrigation. Irrigation plays an important role in farming. 2) The social capital of the farmers is high, the farmers have a good relationship with the government, indigenous people, and farmer groups. Therefore, in addition to providing the physical assistance, the government can also conduct the guidance and socialization on reducing the impact of the climate change through farmer or cultural group.